Investigation of forest area change in the 19th–21st century using military topographic maps - Puzienė, Rūta; Anikėnienė, Asta (International Conference “Environmental Engineering”, 2020)
Long-term changes of the Earth’s cover are imperceptible. Several generations change, people do not see what had been there before they were born, they do not see what happens after they are gone, meanwhile, maps preserve the image of the surroundings that was prevailing hundreds of years ago and the analysis of which allows highlighting certain occurring tendencies. The present study aims at the analysing the change in the forest coverage on the territory of Lithuania employing statistical data and analysing the change in the forest land area from the 19th c. until the 21st c. in the Elektrenai municipality using military topographic maps. During the study, digitalised archival maps and devectorised forest areas were used, and the obtained results were compared. The information provided in the maps reveals a decrease in the forest land area during 19th–20th c. and an increase during the 20th–21st c., however, the current increase has not compensated the earlier decrease.